Embryonic Stem Cell–like Population in Dupuytren's Disease. Issue 11 (November 2016) - Koh, Sabrina P.; On, Nicholas; Brasch, Helen D.; Chibnall, Alice M.; Armstrong, James R.; Davis, Paul F.; Tan, Swee T.; Itinteang, Tinte
Abstract : Background: Recent research has identified mesenchymal stem cells (MSCs) within Dupuytren's disease (DD) tissue and they have been proposed to give rise to the myofibroblasts, implicated in the progression of this condition. The aim of this study was to identify and characterize the primitive population that might be upstream of the MSC population, within DD. Methods: Formalin-fixed paraffin-embedded 4-µm-thick sections of DD cords and nodules obtained from 6 patients underwent 3, 3-diaminobenzidine and immunofluorescent immunohistochemical staining for embryonic stem cell (ESC) markers OCT4, NANOG, SOX2, pSTAT3, and SALL4 and endothelial markers CD34 and ERG. NanoString gene expression analysis was performed to determine the transcriptional activation of these markers. Results: Immunohistochemical staining demonstrated the expression of ESC markers OCT4, NANOG, SOX2, pSTAT3, and SALL4 on the endothelium of the microvessels expressing CD34 and ERG, particularly those surrounding the DD nodules. NanoString analysis confirmed the transcriptional activation of OCT4, NANOG, STAT3, and SALL4, but not SOX2. Conclusion: This article demonstrates the novel finding of an ESC-like population expressing ESC markers OCT4, NANOG, SOX2, pSTAT3, and SALL4, localized to the endothelium of the microvessels within DD tissue, suggesting a potential therapeutic target for this condition. Abstract : Supplemental Digital Content is available in the text.